A model of consumer buying behavior in relation to eco-intelligent products in catering. - Legeza, Darya; Легеза, Дар’я Георгіївна; Brunner, Thomas; Kerimova, Yukilay; Kulish, Tatyana; Куліш, Тетяна Володимирівна; Konovalenko, Anastasia; Коноваленко, Анастасія Сергіївна (My University, 2019)
Growing negative changes cause a deterioration in food quality, which makes peo ple select organic and eco-intelligent food. The aim of the article is to analyze vari ous types of customer behavior using an example of a local catering company that offers eco-intelligent food. The company’s brand operates two catering stores lo cated in different parts of an urban city. The interview of existing and potential cus tomers was conducted within 1,000-meter radius of store locations at peak hours (7:30–10:00 am and 12:00–2:30 pm). The model of consumer behavior is centered on the main principle of deciding to buy eco-intelligent food. The data suggest that customers are looking for additional necessary services, which are vital for eco-in telligent products and expanded selection according to the store’s format. Both the time of the ordering processing and the ability to order a personalized meal have the main influence on customers’ decision. Large selection of eco culinary products in the stores attracts local residents to visit one of these stores at least once a week. An essential feature of a culinary store offering eco-intelligent food is high-quality prepared food. The study recommends expanding promotional programs to give consumers additional knowledge about the advantages of organic nutrition. The prevalent consumer model describes a woman under 40 years old who visits a store at least once a week for lunch and prefers a comfortable environment and a diverse selection of quality eco-food.
Модель купівельної поведінки споживачів по відношенню до еко-інтелектуальних продуктів в громадському харчуванні
Keywords: Ukraine; interview; children’s food; personalized order